'MILK VOLUME, MILK FAT AND CHILDHOOD FRACTURE RISK. (18th May 2018) - Allison, Riley; Maguire, Jonathon
Abstract: BACKGROUND: Children who do not consume cow's milk have been associated with an increased risk of fracture. Cow's milk is consumed by most North American children yet the relationships between the volume of cow's milk consumed, the fat content of cow's milk and childhood fracture risk are unclear. OBJECTIVES: The primary objective was to evaluate whether volume of cow's milk consumed between ages 1 - 3 was associated with fracture between ages 3 - 10. Secondary objectives explored whether milk-fat consumed between ages 1 - 3 was associated with fracture between ages 3 - 10 and whether milk-fat content modified the relationship between milk volume and fracture. DESIGN/METHODS: This was a prospective analysis of 2466 healthy urban children with exposure between 1 and 3 years of age and outcome between 3 and 10 years of age enrolled in the TARGet Kids! -Applied Research Group for Kids cohort. The primary exposure was the volume of cow's milk consumed and the secondary exposure was the average percentage of milk-fat consumed by each child. The outcome was one or more fractures experienced, measured as yes or no. A modified Poisson regression was used to evaluate the relationship between volume of cow's milk at exposure, and one or more fractures at outcome. The same analysis was used to explore the relationship between cow's milk-fat and fracture. Effect modification by milk-fat consumed on the relationship between milk volume and fracture risk was explored by adding an interaction term to the statistical model. RESULTS: In the primary adjusted analysis, a statistically significant association between the volume of cow's milk consumed at exposure and risk of one or more fractures at outcome was not observed (aRR= 1.04; 95% CI: 0.87 to 1.26). In the secondary analysis, a statistically significant association between cow's milk-fat consumed at exposure and fracture risk at outcome was also not observed (aRR= 1.05; 95% CI: 0.84 to 1.31). Cow's milk-fat did not modify the relationship between milk volume and risk of fracture. (p= 0.24). CONCLUSION: In this prospective cohort study of young children, we did not identify a protective effect of early childhood volume of cow's milk or milk-fat consumption on fracture risk in later childhood. Future research in young children is needed to evaluate specific low impact fracture mechanisms, which may be more sensitive to nutritional factors.